Effects of drip irrigation on components of water cycle in arid inland areas: A case study of Manas river basin in northwestern China - Li, Pengfei; Yang, Guang; He, Xinlin; Li, Fadong; Yan, Ke; Wang, Zelin (International Journal of Agricultural and Biological Engineering, 2019)
Compared to either drip irrigation or mulching with plastic film, the two methods together can reduce water requirements of crops grown in arid areas by more than 30%. Such a combination deployed on a large scale (1) reduced the loss of soil water by 31.8% compared to that from drip irrigation alone; (2) narrowed the range of annual evapotranspiration from 1582.4-1780.3 mm, which is average for the basin, to 222.2-294.8 mm; and (3) increased the overall humidity in the central plain of the basin. However, the surrounding regions in which drip irrigation is not combined with mulching are getting more arid; thus, as a result of the water-saving technology, both oases and the desertification of the river basin are increasing at the same time. The results of the study further the understanding of the effects of drip irrigation combined with mulching on water cycles in the basin of the Manas river and suggest ways to protect the ecology and the environment of the basin.Keywords: evapotranspiration, drip irrigation, arid inland areas, water cycle, Mann-Kendall rank test, MOD16, Manas river basinDOI: 10.25165/j.ijabe.20191201.4031Citation: Li P F, Yang G, He X L, Li F D, Yan K , Wang Z L. Effects of drip irrigation on components of water cycle in arid inland areas: A case study of Manas river basin in northwestern China. Int J Agric & Biol Eng, 2019; 12(1): 132–138.